2020
DOI: 10.1002/ijgo.13098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perinatal outcomes after implementation of IADPSG criteria for screening and diagnosis of gestational diabetes mellitus: A national survey

Abstract: Objective To compare perinatal outcomes before and after implementation of the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria for testing of gestational diabetes mellitus (GDM). Methods A national, perinatal, registry‐based cohort study of prospectively collected data was conducted. Patients with diabetes type 1 or 2 were excluded. Outcomes of 135 786 pregnancies before (January 1, 2004 to May 31, 2010) and 140 524 after (June 1, 2011 to December 31, 2017) the introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…However, it should be noted that GDM prevalence (35.5%) and risk factors occurrence in this Spanish population were particularly high compared to those reported in our and other studies study population [32,34,41,43]. Conclusively, countries with high GDM prevalence and risk factor burden might benefit most from adopting of the IADPSG screening criteria to substantially improve perinatal outcomes to an extent of being able to ignore the drawbacks of increased medical cost.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…However, it should be noted that GDM prevalence (35.5%) and risk factors occurrence in this Spanish population were particularly high compared to those reported in our and other studies study population [32,34,41,43]. Conclusively, countries with high GDM prevalence and risk factor burden might benefit most from adopting of the IADPSG screening criteria to substantially improve perinatal outcomes to an extent of being able to ignore the drawbacks of increased medical cost.…”
Section: Discussionmentioning
confidence: 42%
“…In Japan, despite a substantial rise in GDM diagnosis frequency from 2.9% to 13%, a significantly decreased odds were only observed for NICU admission and neonatal hypoglycemia [34]. With a similar change in GDM prevalence (2.6% vs. 9.7%), the introduction of the IADPSG criteria resulted in reduction in incidences of LGA, macrosomia and hypertensive disorders in Slovenian pregnant women [43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, international studies show conflicting results on the effects of screening and treatment of HIP by comparing the one-step approach with the two-step approach. Some studies have reported better pregnancy outcomes [ 3 , 17 , 18 , 19 ], while others have not [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, updated screening and diagnostic practices have played a large role in the additional diagnoses. 1,5,6 Although GDM diagnostic criteria are not consistent worldwide, there has been an increase in universal screening and many countries have updated their criteria in line with the 2010 International Association of Diabetes in Pregnancy Study Group (IADPSG) recommendations. 7…”
mentioning
confidence: 99%